Easing Student Veterans' Transition to Cybersecurity and STEM through a "Math Boot Camp" (Journal of The Colloquium for Information Systems Security Education, 2015)
In this paper, we report on data collected from a group of student veterans who participated in a community college "Math Boot Camp" for student veterans interested in Cybersecurity and STEM fields. The Math Boot Camp combined three levels of remedial mathematics into a single course that relied heavily on interactive, instructional software. The strategic importance of remedial math classes results from the confluence of three factors: the importance of math skills in STEM degrees; veterans' interest in STEM fields; and veterans' actual and/or perceived math skill deficits. We describe the Math Boot Camp and present pre- and post-survey and focus group data collected from the 17 participants. The findings revealed that student veterans entered the Math Boot Camp with a positive view of the importance of mathematics to their lives and were not overly anxious about the course. Fifteen of seventeen students passed the course (2.0 or above). In focus groups, the student veterans commented most frequently about the positive benefits of instructor and the class tutor, the hybrid nature of the course, and the flexibility of placement and advancement afforded by the multi-level classroom. We present implications for design and evaluation of transition courses for student veterans in STEM and policy implication related to Post-9/11 GI bill benefits.